Transplastomic tomatoes expressing double‐stranded RNA against a conserved gene are efficiently protected from multiple spider mites. Issue 4 (9th December 2022) - Wu, Mengting; Zhang, Qi; Dong, Yi; Wang, Zican; Zhan, Wenqin; Ke, Zebin; Li, Shengchun; He, Lin; Ruf, Stephanie; Bock, Ralph; Zhang, Jiang
Summary: Spider mites are serious pests and have evolved significant resistance to many chemical pesticides, thus making their control challenging. Several insect pests can be combated by plastid‐mediated RNA interference (PM‐RNAi), but whether PM‐RNAi can be utilized to control noninsect pests is unknown. Here, we show that three species of spider mites ( Tetranychus evansi, Tetranychus truncatus, and Tetranychus cinnabarinus ) take up plastid RNA upon feeding. We generated transplastomic tomato plants expressing double‐stranded RNA (dsRNA) targeted against a conserved region of the spider mite β‐Actin mRNA. Transplastomic plants exhibited high levels of resistance to all three spider mite species, as evidenced by increased mortality and suppression of target gene expression. Notably, transplastomic plants induced a more robust RNAi response, caused higher mortality, and were overall better protected from spider mites than dsRNA‐expressing nuclear transgenic plants. Our data demonstrate the potential of PM‐RNAi as an efficient pest control measure for spider mites and extend the application range of the technology to noninsect pests.